Effects of the Toxic Dinoflagellate Protoceratium reticulatum on Physiological Rates of Juvenile Scallops Argopecten purpuratus - María Gabriela Nieves; Gonzalo Alvarez; Jesús Antonio López-Carvallo; Paulina Millanao; Michael Araya; Rosario Díaz; Patricio A. Díaz (Fishes)
Protoceratium reticulatum, a dinoflagellate species known for producing yessotoxins (YTX), can form harmful algal blooms (HABs) impacting marine life. This study examined how P. reticulatum influenced the physiological rates and affected the tissue health of juvenile scallops, Argopecten purpuratus. The scallops were exposed to non-toxic algae Isochrysis galbana (diet A) and mixtures where 30 and 70% of the non-toxic algae were replaced by the toxic algae P. reticulatum (diet B and C, respectively) for 15 days, followed by a 15-day recovery period (I. galbana). Results showed that the clearance rate (CR), inorganic ingestion rate (IIR), organic ingestion rate (OIR), and absorption rate (AR) were significantly reduced within the first seven days of exposure to toxic diets, with reductions of approximately 25% and 50% in diets B and C, respectively, compared to the non-toxic diet, and an increase in these parameters during the recovery stage. Histological observations revealed greater tissue damage in the digestive gland than in the gills, with a higher frequency of scallops with severe damage correlating with higher toxic diet content. Despite no direct impact on survival, the compromised physiological health of A. purpuratus juveniles suggests increased vulnerability to other stressors. These findings provide new insights into the filter-feeding behavior and selective filtration capabilities of scallops in the presence of toxic dinoflagellates and how scallops health can be compromised, contributing to the understanding of how HABs and associated toxins affect A. purpuratus.